Educação ambiental e interdisciplinaridade : da explicitação dos conceitos nos PCNs e DCNEM à prática pedagógica no ensino médio - Alves, Suiane Costa (2014)
This research aimed to examine whether the knowledge that students acquire on Environmental Education (EA), at the end of high school, attend to what is set down by the PCNs and DCNEM. The question that guided this research can thus be expressed: to what extent do students who are completing high school have the basic knowledge about EA as proposed by the PCNs and DCNEM? From this central issue, other questions, equally relevant, are presented, such as: What is the concept of interdisciplinarity in EA in PCNs? What is the concept of interdisciplinarity in EA in DCNEM? What is in common between the concepts of EA in PCNs and DCNEM? What is divergent in concepts of EA in PCNs and DCNEM? What are the advances and setbacks between the EA conceptions in the PCNs and DCNEM? How are the concepts of EA reflected in PCNs and DCNEM in the educational practice? What is the place of the EA in the high school curriculum? The method of the research was led by and inductive and deductive approach with qualitative analysis. A field study was also carried as a way to observe student learning in high school. The technique used was a closed questionnaire about the participants’ socioeconomic character, the chemistry teachers’ pedagogical practice and the evaluation of the chemistry learning after the contextualization and interdisciplinarity seen in classroom and their relation with EA. The target audience of the survey was forty students of the 3rd year of a public school CREDE 1 - Maracanaú. The research concluded that students who are completing high school have the required knowledge of the environmental issue as set down by PCNs and DCNEM, nourishing certain ecological awareness of the application of their knowledge in environmentally friendly actions. It further concluded that the knowledge about the contents of chemistry, when contextualized and treated in an interdisciplinary manner, generated learning. As for the specific issues of chemistry that could have leveraged their understanding with the usage of didactic chemistry lab, presented a low hit percentage, just because of the little use of the laboratory and the absence of an investigative approach that could lead the student to reflect on chemistry knowledge. This way, this research produced a manual of chemistry practices with environmental focus and the objective of helping the teacher to contextualize the particular knowledge of this discipline.